2009
DOI: 10.1128/aem.01030-09
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Chemotaxis to Atrazine and Relateds-Triazines

Abstract: Pseudomonas sp. strain ADP utilizes the human-made s-triazine herbicide atrazine as the sole nitrogen source. The results reported here demonstrate that atrazine and the atrazine degradation intermediates N-isopropylammelide and cyanuric acid are chemoattractants for strain ADP. In addition, the nonmetabolized s-triazine ametryn was also an attractant. The chemotactic response to these s-triazines was not specifically induced during growth with atrazine, and atrazine metabolism was not required for the chemota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 58 publications
1
25
0
Order By: Relevance
“…Studies of chemoeffector-MCP assignments in Pseudomonas aeruginosa PAO1 (26 MCPs) and other bacteria (1,14,40) have revealed that many microbes can have a more complicated picture of chemoattractant sensing than is found with the much smaller MCP repertoires of enteric bacteria (31). Therefore, two possibilities are plausible to explain the lack of assignment of a particular MCP to the response toward chitin oligosaccharides.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of chemoeffector-MCP assignments in Pseudomonas aeruginosa PAO1 (26 MCPs) and other bacteria (1,14,40) have revealed that many microbes can have a more complicated picture of chemoattractant sensing than is found with the much smaller MCP repertoires of enteric bacteria (31). Therefore, two possibilities are plausible to explain the lack of assignment of a particular MCP to the response toward chitin oligosaccharides.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research showed that soils amended with fertilizer resulted in greater persistence of E. coli O157:H7, Salmonella enterica serovar Typhimurium, nonpathogenic E. coli, and enterococci (31,32,47), suggesting a potential direct mechanism. Similarly, positive direct effects were anticipated for atrazine, as past in vitro studies have shown that E. coli is chemotactic toward atrazine (33) and can directly utilize atrazine as a nutrient (30,37,66). Atrazine and fertilizer might also cause indirect effects by influencing the algal populations within water bodies.…”
mentioning
confidence: 92%
“…), aliphatic hydrocarbons (Lanfranconi et al . ) and herbicides (Liu and Parales ) in species like Rhizobium sp., Bradyrhizobium sp., Pseudomonas sp., Azospirillum sp., Ralstonia sp., Burkholderia sp. or Flavimonasoryzihabitans .…”
Section: Chemotaxis Of Soil and Aquatic Bacteria: Response To Diversementioning
confidence: 99%